2011
DOI: 10.1021/bc1004125
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Circularly Permutated β-Lactamase Tethered to Antibody Domains by Specific Small Molecules

Abstract: Regulation of enzyme activity either by its substrates or by effectors is generally known as allostery. However, it has been considered hard to alter its effector specificity, despite its potential utility as a sensitive molecular sensor. To this end, we made fusion proteins consisting of an antibody variable region Fv and a circularly permutated TEM-1 β-lactamase cpBLA. Two expression vectors encoding Fv-cpBLA with different antigen specificities were made, in which cpBLA was inserted into the linker region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, in the presence of 1 μM BGP-C10, the specific activity significantly increased and the value was 4.66-fold higher than with no antigen peptide ( p < 0.01). Therefore, the antigen-dependent catalytic behavior of Cbody-cpBLA was clearly implemented, and the dependency is significantly higher than in the Fv-cpBLA that we reported previously …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the presence of 1 μM BGP-C10, the specific activity significantly increased and the value was 4.66-fold higher than with no antigen peptide ( p < 0.01). Therefore, the antigen-dependent catalytic behavior of Cbody-cpBLA was clearly implemented, and the dependency is significantly higher than in the Fv-cpBLA that we reported previously …”
Section: Resultsmentioning
confidence: 99%
“…The pelleted cells were homogenized and centrifuged at 10 000 g for 60 min at 4 °C. The pellet precipitant was solubilized, and the fusion protein was purified with Talon resin (Clontech, Takara-bio) and refolded as previously described . The concentration of purified protein was measured with a Pierce BCA protein assay kit (Thermo scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to mention that the size of the inserted protein has only little impact on the resulting chimeric protein. Indeed, it has been shown that large structured domains can be successfully inserted into β-lactamases, as long as their Nand C-terminal extremities are flexible or close to each other 13,14,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29 . In the present study, the insertion site in BlaP is located far away from its active site and the inserted nanobody has relatively long and flexible extremities (not visible in the X-ray structure) that are located far away from the paratope.…”
Section: Limitations Of the Hybrid β-Lactamase Technologymentioning
confidence: 99%
“…Indeed, recent studies have shown that insertion of antibody variable fragments into the TEM1 β-lactamase results in a chimeric protein that remains able to bind with high affinity to its target antigen. Interestingly, the antigen binding was shown to induce allosteric regulation of TEM1 catalytic activity 11,12 . Furthermore, we showed in several studies that protein domain insertion into a permissive loop of the Bacillus licheniformis BlaP β-lactamase generates functional chimeric proteins that are well suited to monitor protein-ligand interactions 13,14 .…”
mentioning
confidence: 99%